1999
DOI: 10.1097/00001622-199905000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Taxanes as radiosensitizers for head and neck cancer

Abstract: Combinations of paclitaxel and radiation therapy or paclitaxel with other chemotherapy agents and radiation have been tested with variable results in patient populations. To date, three phase I trials have been conducted using paclitaxel alone in combination with radiotherapy for the treatment of patients with head and neck cancer. Dose-limiting toxicity in the 1-hour infusion was mucositis, whereas in the 24-h/wk infusion, fever was the dose-limiting toxicity. In the long-term infusion (24 h/d, 7 d/wk), no do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Inhibition of IkB-a phosphorylation, which blocks IkB-a disassociation from p65/ p50 complexes, downregulates NF-kB and sensitizes cells to DNA-damaging agents (Miyakoshi and Yagi, 2000). Many other results demonstrate that inhibition of NF-kB function increases cell radiosensitivity (Shao et al, 1997;Lee et al, 1998;Herscher et al, 1999;Yang et al, 1999;Kato et al, 2000). We have reported that NF-kB activity is induced by radiation in breast carcinoma MCF-7 cells ) and virus-transformed human keratinocytes (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Inhibition of IkB-a phosphorylation, which blocks IkB-a disassociation from p65/ p50 complexes, downregulates NF-kB and sensitizes cells to DNA-damaging agents (Miyakoshi and Yagi, 2000). Many other results demonstrate that inhibition of NF-kB function increases cell radiosensitivity (Shao et al, 1997;Lee et al, 1998;Herscher et al, 1999;Yang et al, 1999;Kato et al, 2000). We have reported that NF-kB activity is induced by radiation in breast carcinoma MCF-7 cells ) and virus-transformed human keratinocytes (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…A reduction in CDK1/cyclin B1 kinase activity triggers G2/M cell cycle arrest (Cui et al, 2012;Khan et al, 2011). Accumulated evidence has suggested that a lot of radiosensitizing agents worked in different cancers such as taxol (Herscher et al, 1999), oxamate (Zhai et al, 2013) through inducing G2/M arrest via downregulation of cyclinB and CDK1. In the present study, a decrease in the protein levels of cyclin B1 and CDK1 were observed in the combined treatment of fenofibrate with irradiation group.…”
Section: Jia Liu Et Almentioning
confidence: 99%
“…The taxanes had been identified as potential radiosensitizers when preclinical data revealed their lethal effects of inhibiting mitosis, interfering with the cell cycle, and encouraging apoptosis (Herscher et al, 1999). Taxane was shown to have significant activity in patients with metastatic esophageal cancer in the early 1990s (Ajani et al, 1994).…”
Section: Discussionmentioning
confidence: 99%